2018
DOI: 10.1038/aps.2018.32
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the anti-inflammatory effects, pharmacokinetic properties and clinical efficacies of arctigenin and arctiin from Arctium lappa L

Abstract: Arctigenin (AR) and its glycoside, arctiin, are two major active ingredients of Arctium lappa L (A lappa), a popular medicinal herb and health supplement frequently used in Asia. In the past several decades, bioactive components from A lappa have attracted the attention of researchers due to their promising therapeutic effects. In the current article, we aimed to provide an overview of the pharmacology of AR and arctiin, focusing on their anti-inflammatory effects, pharmacokinetics properties and clinical effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(108 citation statements)
references
References 108 publications
1
106
0
1
Order By: Relevance
“…Therefore, various pharmacological effects could be expected from plant compounds, including arctiin and arctigenin. It has been reported that arctigenin and arctiin account for approximately 0.5–2% ( w / w ) and 2–10% ( w / w ) of the dry weight of the AF, respectively [ 29 ]. These compounds also possessed an anti-inflammatory effect.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, various pharmacological effects could be expected from plant compounds, including arctiin and arctigenin. It has been reported that arctigenin and arctiin account for approximately 0.5–2% ( w / w ) and 2–10% ( w / w ) of the dry weight of the AF, respectively [ 29 ]. These compounds also possessed an anti-inflammatory effect.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their chemical structure, phytoestrogens can be classed as isoflavones and lignins. Arctigenin (Ar, Figure 1) is a lignin phytoestrogen extracted from Arctium lappa (Gao, Li, Zhang, & Zeng, 2008) that displays anti-inflammatory (Gao, Yang, & Zuo, 2018), antioxidant (Wu et al, 2014), antifibrosis (Lin et al, 2019), and antitumor effects (Maxwell, Chun, Lee, Kim, & Nam, 2017). In preliminary experiments, we found that arctigenin promotes the differentiation of bone marrow mesenchymal stem cells (BMSCs) of ovariectomized (OVX) rats into osteoblasts, leading to anti-osteoporosis effects.…”
Section: Introductionmentioning
confidence: 99%
“…Some compounds are more sensitive than others and, depending on the time of exposition to high temperatures or pressures, can be degraded. This may justify the lack of arctigenin in our extracts, a compound identified in fractions of A. lappa with an important anti-inflammatory role [35][36][37]. However, the anti-inflammatory activity observed with E1 and E2 extracts of A. lappa may be due to other components, such as lupeol, amyrin, and phytol [31,34,38], which were also found in extracts from A. lappa leaves obtained by pressurized liquid extraction using aqueous ethanol [20].…”
Section: Discussionmentioning
confidence: 99%